All Biomass and UV Protective Composite Composed of Compatibilized Lignin and Poly (Lactic-acid) - Kim, Youngjun; Suhr, Jonghwan; Seo, Hee-Won; Sun, Hanna; Kim, Sanghoon; Park, In-Kyung; Kim, Soo-Hyun; Lee, Youngkwan; Kim, Kwang-Jin; Nam, Jae-Do (Nature Publishing Group, 2017)
Utilization of carbon-neutral biomass became increasingly important due to a desperate need for carbon reduction in the issue of global warming in light of replacing petroleum-based materials. We used lignin, which was an abundant, low cost, and non-food based biomass, for the development of all biomass-based films and composites through reactive compatibilization with poly (lactic-acid) (PLA). Using a facile and practical route, the hydrophilic hydroxyl groups of lignin were acetylated to impose the compatibility with PLA. The solubility parameter of the pristine lignin at 26.3 (J/cm(3))(0.5) was altered to 20.9 (J/cm(3))(0.5) by acetylation allowing the good compatibility with PLA at 20.2 (J/cm(3))(0.5). The improved compatibility of lignin and PLA provided substantially decreased lignin domain size in composites (12.7 mu m), which subsequently gave transparent and UV-protection films (visual transmittance at 76% and UV protection factor over 40). The tensile strength and elongation of the developed composite films were increased by 22% and 76%, respectively, and the biobased carbon content was confirmed as 96 +/- 3%. The developed PLA/lignin composites provided 100% all-biomass contents and balanced optical and mechanical properties that could broaden its eco-friendly applications in various industries.